Cardiac tamponade as an initial presentation of papillary carcinoma with psammoma bodies and intranuclear grooves—A diagnostic dilemma. Issue 9 (23rd May 2019) - Gochhait, Debasis; Sreerekha, Jinkala; Rangarajan, Vidhyalakshmi; Siddaraju, Neelaiah; Govindarajalou, Ramkumar; Penumadu, Prasanth
Abstract: Involvement of body fluids by adenocarcinoma is a common phenomenon. However, metastasis to the pericardial fluid by adenocarcinoma is a rare occurrence. The most common malignancies associated with malignant pericardial effusion are carcinoma of the lung, breast, esophagus, melanoma, lymphoma, and leukemia. Here, we discuss a case of a 36‐year‐old female with hemorrhagic pericardial effusion presenting with cardiac tamponade and psammoma bodies which was suspected and reported as metastatic papillary carcinoma of thyroid on cytomorphology; however, the immunocytochemical and radiological features confirmed metastatic papillary adenocarcinoma of lung contrary to the thyroid which is more common and expected.